THE ROLE OF WOMEN IN THE FAMILY AGAINST THE DISTRIBUTION OF INHERITANCE IN THE CITY OF PALEMBANG - Utami, Iftitah (Nurani, 2020)
The issue of inheritance sometimes becomes a conflict in the community because some heirs do not want to accept the distribution of inheritance that has been determined accordingly furudhul muqaddarah. in the furudhul muqaddarah it is clear the parts of heirs, another case with the distribution of inheritance by customary law where the distribution of inheritance is done through the process of transition from family lineage. The problem in this research is how the views of Palembang IA Religious Court Judges about the Influence of Women's Role in the Family Against the Distribution of Inheritance in Palembang City Communities and How the Views of Palembang City Communities on the Effect of the Role of Women in the Family Against the Distribution of Inheritance in Palembang City Communities. Research Methods in this research are this study uses legal materials obtained from the results of Empirical Juridical research. From the Empirical Juridical research in this study focused on Research on Legal Identification, this research is analytical descriptive, which reveals legislation relating to legal theories that are the object of research. The findings of this study are the view of Palembang City IA Religion Court Judges on the Effect of the Role of Women on the Division of Inheritance for the People of Palembang City is that the Court still determines according to the provisions of Islamic law and the Compilation of Islamic Law (KHI). Palembang City Community's View of the Effect of Women's Role on the Division of Inheritance for Palembang City Communities is the influence of the role of women in terms of the distribution of inheritance. In fact, Palembang custom does not have a role, but just to take a part, but with the times there has been a change but never got more share of women but they are equally equal because of the agreement of fellow heirs for acceptable reasons. Keywords: inheritance, woman inheritance, division of inheritance